Attenuated lipotoxicity and apoptosis is linked to exogenous and endogenous augmenter of liver regeneration by different pathways - Weiss, Thomas S.; Lupke, Madeleine; Ibrahim, Sara; Buechler, Christa; Lorenz, Julia; Ruemmele, Petra; Hofmann, Ute; Melter, Michael; Dayoub, Rania (PLoS ONE, 2017)
Nonalcoholic fatty liver disease (NAFLD) covers a spectrum from simple steatosis to nonalcoholic steatohepatitis (NASH) and cirrhosis. Free fatty acids (FFA) induce steatosis and lipo-toxicity and correlate with severity of NAFLD. In this study we aimed to investigate the role of exogenous and endogenous ALR (augmenter of liver regeneration) for FFA induced ER (endoplasmatic reticulum) -stress and lipoapoptosis. Primary human hepatocytes or hepatoma cells either treated with recombinant human ALR (rhALR, 15kDa) or expressing short form ALR (sfALR, 15kDa) were incubated with palmitic acid (PA) and analyzed for lipo-toxicity, -apoptosis, activation of ER-stress response pathways, triacylglycerides (TAG), mRNA and protein expression of lipid metabolizing genes. Both, exogenous rhALR and cytosolic sfALR reduced PA induced caspase 3 activity and Bax protein expression and therefore lipotoxicity. Endogenous sfALR but not rhALR treatment lowered TAG levels, diminished activation of ER-stress mediators C-Jun N-terminal kinase (JNK), X-box binding protein-1 (XBP1) and proapoptotic transcription factor C/EBP-homologous protein (CHOP), and reduced death receptor 5 protein expression. Cellular ALR exerts its lipid lowering and anti-apoptotic actions by enhancing FABP1, which binds toxic FFA, increasing mitochondrial ?-oxidation by elevating the mitochondrial FFA transporter CPT1?, and decreasing ELOVL6, which delivers toxic FFA metabolites. We found reduced hepatic mRNA levels of ALR in a high fat diet mouse model, and of ALR and FOXA2, a transcription factor inducing ALR expression, in human steatotic as well as NASH liver samples, which may explain increased lipid deposition and reduced ?-oxidation in NASH patients. Present study shows that exogenous and endogenous ALR reduce PA induced lipoapoptosis. Furthermore, cytosolic sfALR changes mRNA and protein expression of genes regulating lipid metabolism, reduces ER-stress finally impeding progression of NASH.
EVALuna2:6907